THE IMPACT OF FAMILY INTERNAL CONFLICT TOWARDS FAMILY BUSINESS DEVELOPMENT (CASE STUDY OF FAMILY BUSINESS PEMANDIAN AIR PANAS CIPANAS – CILEUNGSING) - Ronasih, Ona; Wulansari, Amilia (Journal of Business and Management, 2018)
Abstract. The phenomenon of family business shows a significant influence on the business development of a country including Indonesia. In addition to the results of a survey conducted by KPMG through the European Family Business Trends, almost 80% - 98% of companies in the world are controlled by family companies, 70% of its companies are located in Asia - Pacific where 85% of these companies are family businesses. According to Kompasiana (2002) report, 90% of entrepreneurs in Indonesia are executives running a family business. Despite these facts, APIndonesia (2009) states that in fact most of the family businesses do not have longevity caused by transitions between generations that are not working properly where about 70% of family companies fail in the second generation. Therefore, this study was conducted to analyze the impact of internal family conflicts on the development of the family business itself and find solutions to the problem. This research uses descriptive qualitative method by focusing on coding data obtained from interview and observation. Therefore, the researcher recommends deliberation and compromise to solve the problems incurred in the family while for business interests by implementing a clear business management system and making short and long term plans.